(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The present work is an introductory didactic text on the self-control concept in a behavioralanalytic perspective. It is intended in this work to do a differentiation among the concept used in the common sense and that developed by the behavior analysis, by demonstrating that the mentalist explanations used in the daily life and in psychology itself may hinder the scientific investigation of the self-control behavior. It also aims to discuss the use of this concept and its possible implications and applications by a science of behavior. Finally, it points out the importance of studying self-control, considering that this may be of fundamental importance for the resolution of several problems related to the future of our society.